Interpretação em animação: entre técnicas, estéticas, habilidades e competências - Musarra, Fábio Luiz Livramento Barretto (2022)
"The guiding questions of the thesis are: Is there any character animation process, the need for greater approximation and mastery of resources (skills and competences) arising from interpretation/acting? An animation of fundamental quality that the animator uses observation and interpretation techniques? The training of animation, design and game professionals who consider the need to create animated characters in Brazil disciplines or resources to develop such skills and competences? Has character interpretation been seen as a priority requirement in animation disciplines and manuals/manuals? Thus, the objective is to understand the relationships between character animation processes and resource domains (interpretation/acting and forwarding of didactic contents of their approach). The general objective of this thesis is to understand the relationships between and interpretation of characters and to identify the skills and competences that an animator must acquire for the interpretation of characters. In this way, the specific objectives of reaching the general objective are: Observation, the development of traditional, tradigital, clipping and three-dimensional animation techniques and their relationships with characters and their characteristics. Aesthetics system in animation of characters such as: cartoon, Japanese and realistic, in their particularities in relation to interpretation. Understanding of subjectivity in interpretation in animation and in the corresponding plastics at work, based on references in scenic and aesthetic arts; Presentation of an overview of the curricular series of higher"